Mapa proteômico de espécies filogenéticas do complexo Paracoccidioides - Pigosso, Laurine Lacerda (2012)
The genus Paracoccidioides comprises a complex of phylogenetic species of dimorphic pathogenic fungi, the etiologic agents of paracoccidioidomycosis (PCM), a disease confined to Latin America and of marked relevance in its endemic areas due to its high frequency and severity. The members of the Paracoccidioides genus are distributed in distinct phylogenetic species (S1, PS2, PS3 and 01-like) that potentially differ in their biochemical and molecular characteristics. In this work, we performed the proteomic characterization of different members of the genus Paracoccidioides. We compared the proteomic profiles of Pb01 (01-like), Pb2 (PS2), Pb339 (S1) and PbEPM83 (PS3) using 2D electrophoresis and mass spectrometry. The proteins/isoforms were selected based on the staining intensity of the spots as determined by image analysis. The proteins/isoforms were in-gel digested and identified by peptide mass fingerprinting and ion fragmentation. A total of 714 spots were detected, of which 343 were analyzed. From these spots, 301 represented differentially expressed proteins/isoforms among the four analyzed isolates, as determined by ANOVA. After applying the FDR correction, a total of 267 spots were determined to be differentially expressed. From the total, 193 proteins/isoforms were identified by PMF and confirmed by ion fragmentation. Comparing the expression profiles of the isolates, the proteins/isoforms that were related to glycolysis/gluconeogenesis and to alcohol fermentation were more abundant in Pb01 than in other representatives of the genus Paracoccidioides, indicating a higher use of anaerobic pathways for energy production. Those enzymes related to the oxidative stress response were more abundant in Pb01, Pb2 and Pb339, indicating a better response to ROS in these members of the Paracoccidioides complex. The enzymes of the pentose phosphate pathway were abundant in Pb2. Antigenic proteins, such as GP43 and a 27-kDa antigenic protein, were less abundant in Pb01 and Pb2. The proteomic profile indicates metabolic differences among the analyzed members of the Paracoccidioides genus.